Balancing Work and Values: Key Factors in Reducing Lecturer Burnout - Deswara, Rahmadani Eka; Isnaeni, Ahmad; Purnama, Rahmad (ANFUSINA: Journal of Psychology, 2023)
Lecturers have the main task to carry out the Tridharma of Higher Education which includes teaching and education, conducting research and community service. In addition, there are other activities that lecturers must carry out, such as holding structural positions and becoming members of committees or working groups that carry out activities for faculties or universities. However, in carrying out their duties and responsibilities there are many demands and pressures on lecturers which, when not going well as they should, are thought to encourage the onset of stress which can lead to burnout. This study aims to determine the relationship between work life balance and ethical organization culture with burnout in lecturers. The population in this study were lecturers who were civil servants and PPPK at UIN Raden Intan Lampung. Sampling using accidental sampling technique obtained 103 subjects then analyzed with multiple regression analysis techniques. The results of this study found that work life balance and ethical organization culture jointly affect burnout in lecturers (R = 0.648; F = 36.171; p < .001) with an effective contribution of 42% (R2 = 0.420). So this study concluded that the hypothesis proposed in this study is accepted with the assumption that the higher the work life balance and ethical organization culture in lecturers, the lower the level of burnout in lecturers. Keywords: Burnout, Work Life Balance, Ethical Organization Culture